Parental Reflective Functioning in Mothers and Fathers of Children With ADHD: Issues Regarding Assessment and Implications for Intervention - Mazzeschi, Claudia; Buratta, Livia; Germani, Alessandro; Cavallina, Clarissa; Ghignoni, Roberta; Margheriti, Michele; Pazzagli, Chiara (Frontiers in Public Health, 2019)
Parental factors contribute to ADHD, partly in an etiological way and partly as moderators and mediators of child outcomes and treatment effects. An important aspect of parenting seems to be parental reflective functioning (PRF), defined as the parent's capacity to reflect upon his own and his child's internal mental experience. The studies on parenting factors linked to ADHD have not extensively investigated the role of PRF. Recent findings on interventions have begun to consider mentalization to promote empathy and emotion regulation in parents, but empirical studies assessing PRF are still scarce. The aim of this cross-sectional study was to compare specific familial and parental functioning characteristic between parents of children with attention deficit/hyperactivity disorder (ADHD) and parents of controls without ADHD. A clinical sample of 41 children with ADHD aged 8–11 years and their parents was compared with a matched, non-clinical sample of 40 children. Three aspects of parental functioning were investigated: parental symptomatology, parental alliances and PRF; children's differences in strength and difficulty profiles were also assessed. The results showed that families of children with ADHD had lower socioeconomic status, and both mothers and fathers of the same families reported higher scores for depression and lower PRF than did the control group; only mothers showed lower parental alliance. Logistic regression highlighted the fact that several of these familial and parental factors contributed to the increased risk of belonging to the clinical group, specifically both mothers' and fathers' depressive symptoms and lower PRF. These data represent new findings with potentially meaningful clinical implications for both assessment and intervention.